2015
DOI: 10.1051/0004-6361/201425512
|View full text |Cite
|
Sign up to set email alerts
|

2P/Encke, the Taurid complex NEOs and the Maribo and Sutter’s Mill meteorites

Abstract: Aims. 2P/Encke is a short period comet that was discovered in 1786 and has been extensively observed and studied for more than 200 years. The Taurid meteoroid stream has long been linked with 2P/Encke owing to a good match of their orbital elements, even though the comet's activity is not strong enough to explain the number of observed meteors. Various small near-Earth objects (NEOs) have been discovered with orbits that can be linked to 2P/Encke and the Taurid meteoroid stream. Maribo and Sutter's Mill are CM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…On the other hand, comet 2P/Encke associated with the major stream of Taurids is Xe-type but has a spectrum resembling primitive asteroids (Tubiana et al 2015). The link between Taurids and primitive carbonaceous materials was also supported by the two associated meteorite falls of Maribo and Sutter's Mill (Tubiana et al 2015). Overall, this could imply a similar primitive (C-or D-type) composition of the parent objects of κ-Cygnids and Taurids.…”
Section: Eclipticalmentioning
confidence: 84%
“…On the other hand, comet 2P/Encke associated with the major stream of Taurids is Xe-type but has a spectrum resembling primitive asteroids (Tubiana et al 2015). The link between Taurids and primitive carbonaceous materials was also supported by the two associated meteorite falls of Maribo and Sutter's Mill (Tubiana et al 2015). Overall, this could imply a similar primitive (C-or D-type) composition of the parent objects of κ-Cygnids and Taurids.…”
Section: Eclipticalmentioning
confidence: 84%
“…Popescu et al (2014) studied the spectral properties of the largest asteroids associated with the Taurid complex, but found no evidence supporting mutual relation. Similarly, the spectroscopic and photometric measurements of Tubiana et al (2015) found no apparent link between comet 2P/Encke, the Taurid complex NEOs, and the Maribo and Sutter's Mill meteorites.…”
Section: Introductionmentioning
confidence: 90%
“…There were some speculations that Maribo is related to comet 2P/Encke and the Taurid complex of asteroids, which was, however, not confirmed by spectroscopic observations (Tubiana et al. ). In fact, neither the date of fall nor the semimajor axis is consistent with Taurids.…”
Section: Trajectory and Velocitymentioning
confidence: 95%